Complex Air Heat Exchange of Disc-Shoe (Tubular Type) Brake of Drilling Winch - Volchenko, A.I.; Volchenko, N.A.; Vozny, A.V.; Snurnikov, V.I. (Herald of Azerbaijan Engineering Academy, 2025)
Experimental design developments and theoretical studies of disk-shoe (tubular type) brakes of drilling drawworks with forced air cooling of their friction pairs made it possible to establish the following: improved wear-friction properties of friction pairs due to reduced metal consumption of the main disk and increased area of matte surfaces using an additional disk; forced air heat exchange with the environment of matte and polished surfaces of the main and additional disks by thermal conductivity, convection and radiation was taken into account, which made it possible to estimate the variable value of the brake heat balance; the surface-volume temperature gradient of the friction belts during braking by the main disk of the tubular design is insignificant, and the depth gradient is small in magnitude, which led to uniform wear of the brake friction pairs; the influence of the design parameters of the main and additional brake disks on the weight of the drill pipe string lowered into the well and its operating parameters, from which the braking torque was isolated.